GENETIC DIFFERENTIATION AMONG RED COLORED BOS INDICUS SUBCONTINENT ORIGIN BREEDS USING SNP CHIP DATA - Muhammad Moaeen-ud-Din; Nasir Abbas; Muhammad Sajjad Khan; Arfan Yousaf; Saba Mehreen (Journal of Animal and Plant Sciences, 2024)
In Pakistan, Sahiwal and Cholistani cattle are considered as dairy breeds with traits of disease resistance, heat tolerance, and adaptability to high temperature. These breeds are considered two different breeds although Sahiwal is considered an off shoot of Cholistani cattle. However, these breeds have never been characterized genotypically using SNP data. Moreover, information on genotypic differentiation is unavailable for other subcontinent red colored breeds i.e., Gir, Brahman and Red Sindhi. Thus, present study was meant to investigate distinctive genetic architect if any of these red color breeds of same region of the world. Genotype data of 50K SNP Bead chip was retrieved online from Dryad database. Quality control measures were performed in Plink 1.9 software. Admixture, Principal component analysis and Multidimensional scaling were used for breeds distinction while genetic diversity was estimated using linkage disequilibrium. The genetic structure of these breeds clearly differentiated them from each other performed by admixture analysis from K =2 to K =5. Similarly, all breeds principally differentially scattered in PCA and MDS results. The study revealed different genetic structure for Cholistani and Sahiwal indicating as distinct breeds while Brahman had mixed genetic architect of other Bos indicus subcontinent breeds. The findings of the current study stress for separate genetic improvement program of Sahiwal and Cholistani cattle.
Keywords: Cholistani; Sahiwal; SNPs chip; Admixture; Pakistan